Patient Safety Culture from the Perspective of Nurses Working in Selected Hospitals of Tehran University of Medical Sciences - MR Sheikhy-Chaman (Iran University of Medical Sciences, 2020)
Background & Aims: Quality of care is an important issue in the health system of every country, especially in healthcare centers. The quality of care services encompasses various elements, one of the most pivotal of which is patient safety. Studies have indicated the inadequacy of safety in patient care. Due to the high incidence of medical errors, it is essential to recognize the patient safety culture in the health sector in order to change and modify the existing culture in accordance with recent developments. Safety experts consider the patient safety culture as an inherent element in the promotion of the safety and quality of patient care, and the World Health Organization (WHO) has emphasized on this issue as well. Culture could be defined as the beliefs and values of individuals, which are manifested in their behaviors. The patient safety culture constantly seeks to minimize the adverse events caused by the care provision process in patients, while also indicating the priority of patient safety from the perspective of healthcare employees and their organization. Assessing the current culture could be the starting point for the development of an appropriate safety culture using proper instrument, so that hospital officials would become aware of the status of the patient safety culture and find solutions to improve the culture. The present study aimed to evaluate the patient safety culture among the nurses employed in the selected hospitals affiliated to Tehran University of Medical Sciences, Iran. Materials & Methods: This cross-sectional study was conducted in the late 2019 at seven selected teaching hospitals affiliated to Tehran University of Medical Sciences. Nurses with the minimum clinical experience of one year were enrolled, and those with incomplete questionnaires were excluded from the study. The participants were selected via simple random sampling by the researcher with the cooperation of the nursing manager of each hospital using the random number table. The sample size was determined to be 295 using the Cochranchr('39')s formula, and the share of each hospital was 40-45 nurses. The data collection instrument consisted of two sections; the first section contained the demographic and organizational variables of the nurses, and the second section was the hospital survey on patient safety culture (HSPSC). The HSPSC had 12 dimensions of organizational learning, feedback and communication about error, teamwork within units, supervisor/manager expectations and actions promoting patient safety, frequency of event reporting, non-punitive response to error, staffing, teamwork across units, overall perception of patient safety, communication openness, management support for patient safety, and information exchange and transmission. The HSPSC has been used frequently to evaluate the patient safety culture across the world, and its final version has been translated into Persian by Iranian researchers, the validity and reliability of which have been confirmed. After referring to the research environment and making the necessary arrangements with the hospital officials, the researcher received the permit to enter the wards. In addition, informed consent was obtained from the eligible nurses, and the participants were allowed to withdraw from the research at any stage. Data analysis was performed in SPSS version 16 using descriptive statistics (number, percentage, mean, and standard deviation) and analytical statistics (independent t-test and one-way ANOVA) at the significance level of less than 0.05. Results: Out of 295 distributed questionnaires, 260 (89.8%) were returned. According to the results of descriptive analysis, the mean age of the nurses was 34.14 ± 8.27 years, and the majority were female and married. The mean clinical experience of the participants was 9.98 ± 7.35 years. In addition, the majority of the nurses had a BSc and were employed in general wards. The mean total score of the patient safety culture was 3.06 ± 0.40, with the highest mean scores observed in the dimensions of organizational learning (3.45 ± 0.74), feedback and communication about error (3.44 ± 0.82), and teamwork within units (3.42±0.88). On the other hand, the lowest mean scores belonged to the dimensions of information exchange and transmission (2.45 ± 0.86), management support for patient safety (2.62 ± 0.65), and communication openness (2.87 ± 0.73). The analytical results indicated no significant correlations between the patient safety culture status and demographic and organizational characteristics of the nurses (P>0.05). Conclusion: According to the results, the total score of the patient safety culture was moderate in this study. Among various dimensions of the patient safety culture, the highest and lowest mean scores belonged to the dimensions of organizational learning and information exchange and transmission, respectively. Therefore, it could be concluded that enhancing the safety of care service recipients in health care organizations is influenced by several factors, such as managerschr('39') support for the patient safety culture in hospitals, nurseschr('39') recognition of the patient safety culture, teamwork within organizational units, feedback and communication about errors, staff-related issues, and facilitating information exchange and transmission. Furthermore, promoting interactions, more teamwork within hospital units, and creating a non-punitive environment in order to report more events could be effective in this regard. It is also recommended that the quality improvement unit of hospitals provide appropriate training courses to familiarize nurses with the patient safety culture, implement exams during these courses, and use the feedback to enhance the quality of new and similar training courses. Since this study was only conducted at the hospitals affiliated to Tehran University of Medical Sciences, the results should be generalized to other healthcare centers with caution. For further investigations in this regard, it is suggested that studies be focused on the governmental and non-governmental hospitals of other provinces and larger sample sizes from the perspective of other healthcare employees.